Through the Eyes of the Participant: Making Connections between Researcher and Subject with Participant Viewpoint Ethnography. Issue 2 (May 2016) - Wilhoit, Elizabeth D.; Kisselburgh, Lorraine G.
In this article, we introduce participant viewpoint ethnography (PVE), a phenomenological video research method that combines reflexive, interview-based data with video capture of actual experiences. In PVE, participants wear a head-mounted camera to record the phenomena of study from their point of view. The researcher and participant then review the video together, and the participant narrates and explains salient practices in the video. This generates both naturalistic video data (providing in situ access to social activities) and reflexive discourses on the activity of study. We detail this method, describing PVE data collection, how it differs from similar methods, the advantages of using it in social research, and potential challenges using the example of research on bike commuters. We conclude by suggesting uses for PVE in multiple areas of research.